HUBUNGAN BENTUK TOE BOX TERHADAP KEJADIAN VALGUS PADA GURU SEKOLAH MENENGAH PERTAMA DAN ATAS - Handamari Nursatun Zahra; Sisybania; Muhammad Fathi (Tahta Media Group, 2024)
Background: Teaching is one of the professions that makes a person classified as using formal or non-formal shoes in accordance with the teaching field with a toe box that sometimes does not match the shape of the foot or is smaller than the size of the foot. Toe boxes are divided into three shapes, namely round, square, and pointed toe boxes. The use of shoes with toe boxes that do not match the size of the foot can cause health problems such as the appearance of hallux valgus. Hallux valgus or known as bunion or stiff big toe is a forefoot deformity that causes the Metatarsal Phalangeal Joint (MTPJ) to deviate laterally and the first metatarsal to deviate medially. The purpose of this study was to determine the relationship of toe box shape to the incidence of hallux valgus in junior and senior high school teachers in Jumapolo District. Methods: This study used an analytic observational method with a cross sectional design. The subjects in this study were teachers in junior and senior high schools in Jumapolo District. Sampling using purposive sampling technique with a sample of 27 people consisting of 21 women and 6 men. The research instrument in this study used a goniometer. The independent variable in this study is the shape of the toe box and the dependent variable in this study is hallux valgus. Hypothesis testing in this study used the spearman test. Results: Based on hypothesis testing using the Spearman test, the significance value p=0.000 (p<0.05) was obtained, which can be explained that there is a relationship between the toe box and the incidence of hallux valgus in junior and senior high school teachers in Jumapolo. The results obtained with subjects who experienced hallux valgus were 27 people with subjects who used round toe boxes as many as 2 people, square toe boxes 12 people and pointed toe boxes 13 people. Conclusion: Based on the results of the research conducted, the subjects who experienced hallux valgus were 27 people with subjects who used round toe boxes as many as 2 people, square toe boxes 12 people and pointed toe boxes 13 people in junior and senior high school teachers in Jumapolo District.